Atherosclerotic and Hypertensive Cardiovascular Disease are Associated with Death at Sublethal Carboxyhemoglobin Levels: A Postmortem Study. Issue 3 (19th December 2019) - Conway, Kyle; Rayes, Omar; Brown, Theodore; Webb, Milad
Abstract: Residential fires are a significant cause for morbidity and mortality in the United States. Death is often the result of soot and smoke inhalation causing carbon monoxide (CO) toxicity. The approximate lethal level of carboxyhemoglobin (COHb) in healthy adults has been well described. However, a significant number of medical examiner cases involve infirmed decedents, often elderly, with complex cardiovascular disease burdens. It is well known that death in these cases will occur at sublethal levels of COHb; however, increased lethality has been largely documented via anecdotal experience and lacks quantification. Fifty‐five cases were identified where death resulted from smoke and soot inhalation suffered in a residential fire. The control group, with no cardiovascular disease, had an age‐adjusted mean COHb level of 61.6% at the time of death. Presence of hypertensive cardiovascular disease showed a 30% reduction in COHb (age‐adjusted mean 43.2%), atherosclerotic disease showed a 33% reduction (age‐adjusted mean 41.5%), and combined disease presentation accounted for 41% reduction (age‐adjusted mean 36.3%). When controlling for age, atherosclerotic and hypertensive cardiovascular diseases were each associated with statistically significant decreases in COHb ( p  < 0.01). Increasing age was associated with decreased COHb levels at 2.8% per 10 years of life ( p  < 0.01), even when modeled with hypertensive and atherosclerotic disease. These findings carry important public health significance, as well as practical significance for the medical examiner when interpreting COHb levels in cases of suspected deaths due to smoke and soot inhalation.